Review and multi-criteria assessment of solar energy projects in Chile. (June 2016) - Grágeda, M.; Escudero, M.; Alavia, W.; Ushak, S.; Fthenakis, V.
Abstract: Chile needs to increase its installed electric capacity to support economic growth. Currently, the total demand is 67, 564 GW h and an additional 22, 508 GW h will be needed by 2020 to meet the energy demand of industrial projects. The Chilean mining industry is a major electricity consumer in the country accounting for one third total consumption over today. Solar energy has the highest potential for growth in northern Chile as the north of the country hosts the highest solar resources of the world. In this paper we present a comprehensive review of the energy supply and demand status, planning and prospects in the country with focus on solar photovoltaic- and solar thermal-projects. As of the end of 2014, a solar capacity of 2384 MW are operational and under construction, and more than 10, 000 MW of solar power plants have been proposed; most solar projects are located in northern regions where the mining takes place. Considering a conservative scenario where one half of the proposed solar projects would be operational before 2020, solar technology could cover a great part of the country's energy requirements. We evaluated eight operating PV plants and three operating solar thermoelectric plants based on a multi-criteria assessment to offer a reference point for assessing future projects.